Koro-like Syndrome beyond Asia: Case Report of a Female from Jos, Nigeria - Saleh, Dauda Akwai; Lekwai, Augustine James; Morris, Ruth Emibarsa; Paul, Benmun David; Zwandor, Jerome Nanjul; Daniang, Honaan Andrea (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025, 2025)
Koro is a culture-bound syndrome characterized by acute anxiety and the belief that one’s genitalia is retracting into the body, which may lead to death. The syndrome is a culture-bound disorder commonly reported among men in Asia, Koro-like presentations have also been documented globally, with few cases involving women. This paper presents a case report of a 22-year-old single female in Jos, Nigeria, who experienced sudden anxiety and perceived genital disappearance after an encounter with a stranger. Examination of the genitalia by one of the researchers revealed that the genitalia were intact, psychological first aid was provided. Further medical evaluation confirmed that her genitalia were intact. The case is discussed within the framework of anxiety and delusional disorder theories, including the four-factor theory of anxiety, and two-factor theory of delusion, with emphasis on sociocultural influences, observational learning, and cognitive bias. This report underscores the importance of differentiating between culture-bound syndromes and medically verifiable genital pathology, highlights the role of psychoeducation in dispelling harmful beliefs, and calls for public awareness to prevent mob violence against alleged perpetrators of “genital theft.” The findings contribute to cross-cultural psychiatric literature by documenting a rare presentation of Koro-like syndrome in a Nigerian female. Keywords: Koro-like Syndrome, Asia, Case Report, Female, Jos, Nigeria